Practical and Ethical Dilemmas in Researching Sensitive Topics with Populations Considered Vulnerable - Hilário, Ana Patrícia; Augusto, Fábio Rafael (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book seeks to support social science researchers who interact with vulnerability and/or sensitivity in the context of their research. Whilst there has been some important debate about the theoretical, methodological and ethical issues of conducting research on sensitive topics, and/or with vulnerable populations, the number of scholarly publications focused solely on these topics is limited and not up to date. The book intends to fill this gap by providing various research experiences, as well as the elements that characterize them. The articles selected for this book intend, first and foremost, to stimulate reflexivity amongst the use of the concepts of sensitive topics and vulnerable groups, and to provide tools that will allow researchers to improve their research practices The book integrates several articles that explore a wide range of dilemmas that, to a certain extent, might allow the reader to access the backstage of this type of research. The reader will find here a rich and fruitful space for theoretical and empirical reflection, where several social science researchers with different backgrounds share their experiences and research paths in a rigorous and creative way.